2015
DOI: 10.1016/j.rboe.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of surgical treatment for hip fractures among the elderly in Brazil

Abstract: ObjectivesTo estimate the cost per quality-adjusted life-year (QALY) focusing on the length of time between trauma and surgery.MethodsA retrospective cohort with systematic sampling was conducted among all the patients who were admitted to the study hospital through the Brazilian National Health System (SUS) over a three-year period. Two treatment strategies were compared: early treatment, if the patient was operated up to the fourth day; and late treatment, if this was done after the fourth day. The cost was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Hip fracture in the elderly is considered a public health issue worldwide [7] , [8] . Increased mortality and morbidity, besides increased treatment costs, with very poor results have been described [6] , [9] . There are few reports in the literature that assess the results and costs of this condition in chronic kidney dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hip fracture in the elderly is considered a public health issue worldwide [7] , [8] . Increased mortality and morbidity, besides increased treatment costs, with very poor results have been described [6] , [9] . There are few reports in the literature that assess the results and costs of this condition in chronic kidney dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is believed that this exponential increase is closely related to a higher life expectancy, since the associated risk factors become more prevalent as people grow older. 8 In Brazil, Loures et al 9 found an average total cost of BRL 1,933.79 for patients submitted to surgical PFF correction in the public health system in 2011 and in 2012. In the 2007/2008 period, there were 34,284 intertrochanteric femoral (FIT) fractures in Brazil, and their treatment costed a total of ∼ BRL 30.8 million in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…7 Acredita-se que este incremento exponencial tenha íntima relação com o aumento da expectativa de vida, uma vez que os fatores de risco associados tornam-se mais prevalentes ao decorrer do envelhecimento do indivíduo. 8 No Brasil, Loures et al 9 encontrou custo médio total de R$ 1.933,79 para os pacientes submetidos a tratamento cirúrgico para correção de FPFs na rede pública, tendo como base os anos de 2011 e 2012. No biênio 2007/2008, também no Brasil, o número de fraturas intertrocanterianas do fêmur foi de 34.284, sendo o gasto público total no ano de 2008 para custeio do tratamento dessas fraturas de aproximadamente R$ 30,8 milhões.…”
Section: Introductionunclassified
“… 12 Thus, both OA and balance alterations in the elderly increase the risk of falls and fractures, leading to negative functional consequences and economic impact on society due to their high morbidity and mortality. 13 …”
Section: Introductionmentioning
confidence: 99%